Effects of the fundamental oxide properties on the electric field-flash temperature during flash sintering. (1st April 2019) - Chaim, Rachman; Estournès, Claude
Abstract: Flash sintering of oxide powders is associated with dissipated power in the narrow range 10–50 W·cm −3 irrespective of their composition. By analysis and normalization of the experimental results from literature to constant particle size (100 nm) and applied electric field (500 V cm −1 ), we show that the relative flash sintering temperature is dictated by the oxide crystal-type and its cation ionic potential resulting from its chemical composition. The expected flash onset temperature increases with the increase in fusion enthalpy and confirm the formation of liquid at the particle contacts as a mechanism for the powder densification. Graphical abstract: The flash onset temperature of oxide primarily dictated by its crystal-type, its average ionic potential and fusion entropy.Unlabelled Image